Molecular beam epitaxy grown Ge/Si pin layer sequence for photonic devices - Schulze, J.; Oehme, Michael; Werner, J. (Thin Solid Films, 2012)
A key challenge to obtain a convergence of classical Si-based microelectronics and optoelectronics is the manufacturing of photonic integrated circuits integrable into classical Si-based integrated circuits. This integration would be greatly enhanced if similar facilities and technologies could be used. Therefore one approach is the development of optoelectronic components and devices made from group-IV-based materials such as SiGe, Ge or Ge:Sn. In this paper the optoelectronic performances of a pin diode made from a Ge/Si heterostructure pin layer sequence grown by molecular beam epitaxy are discussed. After a detailed description of the layer sequence growth and the device manufacturing process it will be shown that - depending on the chosen operating point and device design - the diode serves as a broadband high speed photo detector, Franz-Keldysh effect modulator or light emitting diode. © 2011 Elsevier B.V. All rights reserved.
CRIS-Team Scopus Importer:2021-06-29
Keywords: Ge emitter; Ge modulator; Ge pin photodiode; Ge/Si heterostructure; Molecular beam heteroepitaxy; Optoelectronic